Manifestasi Sikap Politik Yesus Di Jemaat Imanuel Taripa - Mbaloto, Putri Chrisdwienjel (Sekolah Tinggi Teologi Kadesi Bogor, 2025)
The manifestation of Jesus' politics is a politics rooted in justice, love, liberation, and solidarity with the oppressed values that serve as a reference for the Imanuel Taripa Congregation in practicing their own approach to politics. Talking about politics refers to governance, whether in society or within the church, and also involves discussions about politicians, strategies, and power. This study employs a qualitative methodology to gain a deep understanding of the issues at hand. The choice of this approach is based on its relevance to the nature of the research topic, which focuses on interpretation and existing social dimensions. To strengthen the analysis, the author uses two data collection techniques: field research through interviews and literature studies. The political process within the church at the Imanuel TaripaCongregation takes place silently, including the regulation of church leadership structures, eventually leading to dominance over church governance. The state represents a form of power, and the government is a manifestation of developed authority. Therefore, the Imanuel Taripa Congregation, which is also part of the village community, inevitably interacts with the government. Although many events show politics being used selfishly to gain power, this paper seeks to reveal how Jesus’ politics should function within the congregation so that no individual acts as if they hold greater authority.